2021
DOI: 10.3892/ol.2021.13176
|View full text |Cite
|
Sign up to set email alerts
|

Function of BCLAF1 in human disease (Review)

Abstract: Originally identified as a regulator of apoptosis and transcription, B-cell lymphoma-2-associated transcription factor 1 (BCLAF1) has since been shown to be associated with a multitude of biological processes, such as DNA damage response, splicing and processing of pre-mRNA, T-cell activation, lung development, muscle cell proliferation and differentiation, autophagy, ischemia-reperfusion injury, and viral infection. In recent years, an increasing amount of evidence has shown that BCLAF1 acts as either a tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 121 publications
(429 reference statements)
0
12
0
Order By: Relevance
“…Another highly abundant immunopeptide is from BCLAF3 (regulator of apoptosis and transcription, B‐cell lymphoma‐2‐associated transcription factor 3). BCLAF1 is associated with a multitude of biological processes, such as DNA damage response, splicing, and processing of pre‐mRNA, T‐cell activation, lung development, muscle cell proliferation and differentiation, autophagy, ischemia–reperfusion injury, and viral infection 55 . In a mouse model, BCLAF3 may induce differentiation in gastric glands by suppressing Wnt signalling and Reg family gene expression.…”
Section: Resultsmentioning
confidence: 99%
“…Another highly abundant immunopeptide is from BCLAF3 (regulator of apoptosis and transcription, B‐cell lymphoma‐2‐associated transcription factor 3). BCLAF1 is associated with a multitude of biological processes, such as DNA damage response, splicing, and processing of pre‐mRNA, T‐cell activation, lung development, muscle cell proliferation and differentiation, autophagy, ischemia–reperfusion injury, and viral infection 55 . In a mouse model, BCLAF3 may induce differentiation in gastric glands by suppressing Wnt signalling and Reg family gene expression.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, Kbz may be associated with diseases such as cancer. B cell lymphoma-2-associated transcription factor 1 (BCLAF1), a death-promoting transcriptional repressor, participates in various biological processes, including autophagy and DNA damage response, and is highly associated with the proliferation and drug-resistance of cancer ( Mou et al., 2020 ; Yu et al., 2022 ). Notably, it contains eight Kbz sites, therefore linking Kbz to tumor development.…”
Section: Resultsmentioning
confidence: 99%
“…BCLAF is a multifunctional protein with an arginine-serine functional domain (RS domain) and DNA binding domain [28,29]. It plays an important role in various physiological processes in cells, including apoptosis, lung development, T cell activation, autophagy, DNA repair, and transcriptional regulation [30]. It was reported that dysregulated expression of the BCLAF1 is closely associated with cancer, and overexpression in Hela cells caused apoptosis, which implied that BCLAF1 could induce apoptosis [31].…”
Section: Discussionmentioning
confidence: 99%